Combined artificial intelligence, sustainable land management, and stakeholder engagement for integrated landscape management in Mediterranean watersheds. Issue 145 (July 2023) - Ruiz, Itxaso; Pompeu, João; Ruano, Antonio; Franco, Paloma; Balbi, Stefano; Sanz, María J.
Abstract: In the context of water scarcity, soil erosion, and biodiversity decline, the Mediterranean basin urges to manage its nearly hundred coastal watersheds in a coordinated manner. To this end, we propose an integrated approach to model socio-ecologic scenarios with Sustainable Land Management (SLM) options at the watershed scale to strengthen the functioning of multiple Ecosystem Services (ES). This is tested in the Mijares watershed in eastern Spain. As a first step, we propose using integrated modeling technology to quickly assess areas of ecosystem goods and services supply and demand within the case study. To this end, we applied ARIES, an AI-driven online modeling platform widely used in the ES community. Then, we use this information to identify suitable SLM options documented in the WOCAT global database for providing the identified ES. Lastly, to adjust the results to the social-ecological context, we carry out consulting and participatory processes with key stakeholders to incorporate local knowledge of ES and capabilities to adopt SLM measures into the final proposal. As a result of this work, we can model various SLM scenarios, easing decision-making toward more integrated and sustainable land management in the watershed. Given the reproducibility of the used methodologies, our approach can be adopted in other Mediterranean contexts. Highlights: We present an innovative approach to strengthen the functioning of ES through SLM. We select the study case of the Mijares watershed in E Spain to exemplify its use. Quantifiable changes on ES result from modeling SLM options based on stakeholder engagement. Results are accessible to stakeholders and policy-makers.